Furnishings and decorations of a children's room - Sweet, Helen (My University, 1908)
Introduction: The developments and improvements which mark the advance of knowledge in all lines also mark the advance along the art of child development both physically and mentally. The more advanced the age becomes the more carefully are the children reared and the more completely are they surrounded from the first by influences which will bring out the best in them and foster a spirit of love for the good and beautiful.
Citation: Sweet, Helen. Furnishings and decorations of a children's room. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Children; Design; Bedrooms; Décor; Graduating theses; Senior theses; Theses